Serangan Timur Lenk Pada Masa Sejarah Kemunduran Peradaban Islam - Muhammad Basri; Amanah Putri Fadillah; Fannia Sri Juwita; Mivtahul Zannah (LPPM Politeknik Pratama, 2024)
Tamerlane's attacks greatly influenced the lives and efforts of Islamic da'wah throughout the world. Its effects included the surrender of almost all Muslim territory to the Mongols in a short time, the destruction of major cities such as Baghdad, Samarkand, Bukhara, and Kairat, the destruction of many Islamic mosques, works of art, and science, oppression by Mongol rulers who did not respect Islam, and loss of political and administrative continuity in the Muslim world. When Mongols from the interior of Siberia invaded Muslim territory in the 13th century, it was known as Tamerlane's Incursion. This was one of the reasons the Abbasid dynasty collapsed, which at the time was considered a symbol of Islamic power and progress throughout the world. The influence of Chinese religion and culture, civil wars between Mongol tribes, the political and economic goals of Genghis Khan and his descendants, and competition with other countries such as Persia, India, and Europe were some of the factors that contributed to this attack. Tamerlane's attacks also taught Muslims to unite and fight against their enemies. Apart from maintaining ethical and moral principles in accordance with Allah's Shari'a, Muslims must strengthen their country's identity as an Islamic country and develop research and technology that is beneficial for human welfare.